Nexus between country governance, globalization, sustainable development policy, fair trade and economic sustainability: a mediation-moderation approach - Wang, Hanning; Li, Shunyi; Zhang, Hongfeng (Technological and Economic Development of Economy, 2024)
Sustainable development of the economy is the goal of every country in the world. The economic growth of China is accepted worldwide, but the Chinese economy also suffers from an economic crisis. The role of the Chinese government is important for chinses businesses and the economic sustainability of the country. The theoretical framework of this study is designed to determine the impact of globalization and sustainable development policy on fair trade and economic sustainability in China. A questionnaire based on Likert scale were employed with a random sampling technique to collect the cross-sectional data for this research and 1094 responses were collected at the rate of 55%. AMOS statistics tool was employed for the findings of this study based on a research questionnaire. The research concludes that globalization and sustainable development policy have a significant impact on fair trade and economic sustainability in China. This study introduced a new framework related to economic sustainability in the body of knowledge. The theoretical and practical implications of this study have significance for literature and practitioners in China to achieve sustainability in the economy. The research is novel as it highlighted the importance of globalization and sustainable development policy for fair trade and economic development in China. Accordingly, it would be helpful for the policy makers to have reliable decisions for sustainable development and promotion of fair trade.